2016
DOI: 10.1590/1678-4685-gmb-2015-0273
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental ancestry markers in Chilean populations

Abstract: The presence of Native Americans, Europeans, and Africans has led to the development of a multi-ethnic, admixed population in Chile. This study aimed to contribute to the characterization of the uniparental genetic structure of three Chilean regions. Newborns from seven hospitals in Independencia, Providencia, Santiago, Curicó, Cauquenes, Valdívia, and Puerto Montt communes, belonging to the Chilean regions of Santiago, Maule, and Los Lagos, were studied. The presence of Native American mitochondrial DNA (mtDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…At regional level, the relatively high preservation of the Native American ancestry obtained in current urban Patagonia populations might be related to the late incorporation of this region to the National State (Law 1584, 1884), which allowed the Native populations to keep their autonomy for longer. Also, it might be related to the high migratory flow that the Patagonia region received from the inland provinces and from bordering countries, mainly Chile, with high Native American genetic background [4,36–38].…”
Section: Resultsmentioning
confidence: 99%
“…At regional level, the relatively high preservation of the Native American ancestry obtained in current urban Patagonia populations might be related to the late incorporation of this region to the National State (Law 1584, 1884), which allowed the Native populations to keep their autonomy for longer. Also, it might be related to the high migratory flow that the Patagonia region received from the inland provinces and from bordering countries, mainly Chile, with high Native American genetic background [4,36–38].…”
Section: Resultsmentioning
confidence: 99%
“…The estimates on the Chilean population were based mostly on studies of a few urban centers and very few regions of the autosomal genome. Studies using genetic markers with uniparental inheritance have shown an asymmetrical admixture of the ancestral European and Amerindian genomes by sex, as a consequence of Spanish men mating with Amerindian women during the first century of colonization, which has produced 84% Amerindian mitochondrial DNA [12] and less than 20% Amerindian Y chromosomes in the current Chilean population [13,14]. This asymmetrical admixture has also been demonstrated for other contemporary Latin American populations [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, one Robinson Crusoe Islander was found by Y-Fitter to carry the R1 haplogroup (defined by M173) which is basal to the common European subclades R1a and R1b. R clade haplogroups are common in both North ( Malhi et al, 2008 ) and South American indigenous ( Vieira-Machado et al, 2016 ) populations. They are the second most common Y haplogroup detected in South American males ( Malhi et al, 2008 ) and is considered to be as a result of early European colonization ( O’Rourke and Raff, 2010 ; Vieira-Machado et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both these rates of indigenous haplogroups are substantially lower than those reported by previous studies of Chilean populations. Vieira-Machado et al (2016) reported 88.2% indigenous mitochondrial haplogroups from individuals tested in a number of hospitals in Santiago. Similarly, Rocco et al (2002) found 84% of mitochondrial haplogroups were indigenous in a mixed Santiago population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation